PENGEMBANGAN POTENSI PARIWISATA MELALUI WISATA EDUKASI DI KAMPUNG BUDAYA SAMIN BOJONEGORO - Ahmad Hanafi; Sheidy Yudhiasta (Journal Publicuho, 2024)
One of the tourist attractions developed in the Samin Cultural Village which is located in Japanese Hamlet, Margomulyo Village, Margomulyo District, Bojonegoro Regency is through educational tourism on the cultivation of matoa fruit and crystal guava. The development of this educational tourism began with outreach activities to local pokdarwis to plant matoa fruit and crystal guava seeds in the camping area. The research method used by the author is qualitative research. The data collection technique used in this research is through direct observation, interviews, recording documents and journal articles. Interactive data analysis techniques. The research results show that with a variety of natural and cultural tourism potential, this village is developing educational tourism about matoa fruit and crystal guava, which are suitable for planting in the area. This development involves outreach and planting seeds, aimed at increasing tourist visits and community income.